Bioautography and FTIR Analysis of Ethanol Fraction Morel Berry Root (Physalis angulata L.) Against Staphylococcus epidermidis and Pseudomonas aeruginosa - Pratika Viogenta; Latifah Megasari; Laila Susanti (Majalah Obat Tradisional, 2022)
Morel berry root contains flavonoids, tannins, and alkaloids that have an antibacterial characteristics. This study aims to determine the antibacterial activity of the morel berry root ethanol fraction against Staphylococcus epidermidis and Pseudomonas aeruginosa and the most effective active compounds to inhibit such activity. Extractions of morel berry root used the maceration method with ethanol 70% of and then continued by fractionation using ethanol, chloroform, and n-hexane. Test of the compound fraction was performed using Thin Layer Chromatography (TLC) and characterization with FTIR Spectrophotometer. The results of the antibacterial activity with inhibitory zone diameter were at a 100% concentration of 18.69 mm in S. epidermidis while P. aeruginosa of 20.00 mm. Bioautographic results for ethanol fraction indicate an inhibited zone with an Rf value of 0.72 in the S. epidermidis and P. aeruginosa which is thought to be a flavonoid compound. Characterization with FTIR spectrophotometer functional groups O-H phenol, C = C aromatic, C-H aromatic, C-O alcohol, and C-H aliphatic in ethanol fraction with Rf 0.72.